Effects of Thermal Bio-Oil Immersion Process on Antilarvicidal, Anisotropic, Mechanical, and Thermal Properties of Turkish Pine Wood - Ahmet Ali Var (BioResources)
Engineering properties of Turkish pine wood were evaluated to determine effects of a bio-oil thermal immersion process. Wood samples were impregnated with linseed oil, castor oil, and a mix of both oils. The investigation encompassed antilarvicidal activity, bending and compressive strength, anisotropic swelling, thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy. Linseed and castor oils demonstrated potent antilarvicidal properties, achieving 100% and 92% mortality rates, respectively. The mixed oil exhibited 79.2% mortality. The thermal immersion treatment significantly enhanced the bending and compressive strength, and linseed oil yielded the highest improvements at 28.7% and 77.0%, respectively. Anisotropic swelling notably decreased. The linseed oil showed the greatest reduction (7.1%) and the mixed oil the least (2.7%). TGA results indicated improved thermal stability, with weight losses of 1.7%, 2.0%, and 2.2% for linseed oil, castor oil, and mixed oil, respectively. FTIR analysis revealed new peak regions ranging from 1159 to 3398 cm⁻¹ and suggested significant interactions between the bio-oils and the cell wall components, particularly for linseed oil. In conclusion, the thermal bio-oil immersion treatment effectively improved the selected properties of this wood.